Green Moral: Nature Concervancy Strategy For Communities At Diloniyohu And Sidomulyo Selatan Villages, Boliyohuto District, Gorontalo Regency - Herson Kadir; Wa Ode Irawati (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This community service is conducted through The Thematic Community Service Program “Village Building”. This program is related to Green Moral Concept by applying nature conservancy strategy by people at Diloniyohu and Sidomulyo Selatan Village, Boliyohuto District, Gorontalo Regency, to accomplish the achievement of SDGs. The implementation of the program is conducted together by the university students, local communities and government. The main objective of this Thematic Program is to increase the community’s understanding and attitude about nature conservancy through Green Moral strategy. This strategy is impelemented by doing socialization and education to community as a part of character education to build their awareness to conserve environment which is in line with SDGs program. This Thematic Community Service Program has a beneficial effect to assist local government and community in making policies and planning various program in relation to the strategy to conserve the nature and village environment. The program is implemented thorugh the following methods, preparation, briefing, and implementation. The result of the program has been accomplished by forming “Youth and Community for Environmental Care”, arrange the frontyard by growing bamboo hydroponic plants, ecobricks, and distributing stickers “Care the Environment” to people as an effort to raise their awareness of conserving the nature and environment. Keywords: Green Moral, nature, Sidomulyo Selatan, Diloniyohu